HUBUNGAN PELAYANAN PRIMA (EXCELLENT SERVICE) PERAWAT DENGAN KEPUASAN PASIEN DI INTENSIVE CARE UNIT RSUD SYAMRABU BANGKALAN - Qurrotu Aini (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2019)
Satisfaction is the feeling that arises in the patient when the service has exceeded expectations. Based on preliminary study conducted on March 14, 2017 it was found that the level of patient satisfaction in the category enough as many as 6 (60%) respondents. The purpose of this study was analyzed the relation excellent service nurse to the patient satisfaction in Intensif Care Unit RSUD Syarifah Ambami Rato Ebu Bangkalan. The design of this study was analytic corelative using a “Cross sectional”. The study population was all patiens treated in the Intensif Care Unit RSUD Syarifah Ambami Rato Ebu Bangkalan. The sample was 23 respondents. The sample used non-probability sampling by quota sampling. Independent variables was excellent service nurse and dependent variables is satisfaction patient. The collected data used a questionnare then it was analyzed by Spearman Rank with α = 0,005. The results showed June, 2017 that nurses who did good excellent service and satisfied patient by 8 (34,8%) respondents, and performed excellent service nurse less and patients were unsatisfied as much as 1 (4,3%) respondent. Spearman rank statistical test showed that ρvalue =0,042 < α=0,05 which mean there was a relation between excellent service nurse to the patient satisfaction in Intensive Care Unit RSUD Syarifah Ambami Rato Ebu Bangkalan. For health workers, especially nurses to pay more attention and understand about the excellent service that refers to patient satisfaction. So, the patient can recover from his illnes thanks to the encouragement and support of the nurse and is statisfied with the service provided by the nurse